Correlation of Serum Alkaline Phosphatase, Lactate Dehydrogenase, C-Reactive Protein, Blood Deposition Rate, ?-Hcg Expression and Tumor Volume to Lung Metastasis Risk in Osteosarcoma Patients - Achmad Fachrizal1, Dwikora Novembri Utomo1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Osteosarcoma is the most common type of sarcoma that found in bone. The survival rate in osteosarcoma patients was less than 20.00% at the end of 1980 but is currently increasing to over 70.00% for nonmetastatic patients. The objective to analyze the correlation between Lactate Dehydrogenase (LDH), Alkaline Phosphatase (ALP), C-Reactive Protein (CRP), Blood Deposition Rate (LED) , hCG expression and tumor volume with pulmonary metastases in osteosarcoma patients. The subjects were osteosarcoma patients that the data taken from January 2015 to December 2016. The subjects will be clinical, radiological (plain, CT scan thorax, MRI) examinations, serum marker tests consisting of ALP, LDH, CRP and LED and histopathologic staining IHC ?-hCG. The study design was cross-sectional, while the statistical analysis used was normality test, Spearman correlation, chi-square test and logistic regression. The results majority of subjects were male (52.00%) and aged 11-20 years (85.00%). The tumor volume (p = 0.07), LDH levels (p = 0.07), and ALP levels (p = 0.016) were statistically significant for pulmonary metastases with moderate correlation (r = 0.587; 0.587; 0.53). The tumor volume was the most sensitive biomarker to diagnose lung metastasis in osteosarcoma patients (p = 0.171). Conclusion among other protein biomarkers, tumor volume was most sensitive in diagnosing pulmonary metastases. The volume of the tumor will increase the risk of pulmonary metastases in osteosarcoma patients.